Structure and topology around the cleavage site regulate post-translational cleavage of the HIV-1 gp160 signal peptide - Snapp, Erik Lee; McCaul, Nicholas; Quandte, Matthias; Cabartova, Zuzana; Bontjer, Ilja; Källgren, Carolina; Nilsson, IngMarie; Land, Aafke; von Heijne, Gunnar; Sanders, Rogier W; Braakman, Ineke (eLife, 2017)
Like all other secretory proteins, the HIV-1 envelope glycoprotein gp160 is targeted to the endoplasmic reticulum (ER) by its signal peptide during synthesis. Proper gp160 folding in the ER requires core glycosylation, disulfide-bond formation and proline isomerization. Signal-peptide cleavage occurs only late after gp160 chain termination and is dependent on folding of the soluble subunit gp120 to a near-native conformation. We here detail the mechanism by which co-translational signal-peptide cleavage is prevented. Conserved residues from the signal peptide and residues downstream of the canonical cleavage site form an extended alpha-helix in the ER membrane, which covers the cleavage site, thus preventing cleavage. A point mutation in the signal peptide breaks the alpha helix allowing co-translational cleavage. We demonstrate that postponed cleavage of gp160 enhances functional folding of the molecule. The change to early cleavage results in decreased viral fitness compared to wild-type HIV.
Keywords: konformace proteinů; Cell Line; HIV Envelope Protein gp160; proteiny - lokalizační signály; transport proteinů; Protein Sorting Signals; lidé; HIV-1; proteolýza; buněčné linie; HIV obalový protein gp160; Protein Conformation; Protein Transport; sbalování proteinů; Protein Folding; Proteolysis; Humans